An Empirical study on Impact of Pandemic on Financial Health of Family living in Palghar District - Raval, Dr. Jaydip; Trehan, Dr. Gautam; Yadav, Miss. Sonam (The journal of contemporary issues in business and government, 2022)
The research article is aimed at understanding, analysing and interpreting the impact of Pandemic on Financial Health of Families. Researcher has collected Primary data in this empirical study giving more insights and true picture of financial challenges and income volatility faced by families living in Palghar District. The district is relatively new and comes in rural belt. Therefore, it will also give reader (Corporates, Govt. Body, Academicians, Researchers and Citizens) knowledge and understanding of the financial implications in semi-urban and rural belt. The research covers key parameters and factors such as Earning members, Salary Cut, Borrowing, Change in Income and Loss of Employment which have significantly affected the financial health of family in the Palghar District.